1969
DOI: 10.1111/j.1528-1157.1969.tb06141.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐existence of Focal and Bilateral Diffuse Paroxysmal Discharges in Epileptics: Clinical‐electro graphic study

Abstract: SUMMARY Thirty‐five epileptic patients with co‐existent focal and bilaterally synchronous, diffuse paroxysmal electrographic discharges are evaluated and their electrographic features are correlated with clinico‐pathological data. The findings are compared with information derived from a control group of 67 patients with clearly defined and uncomplicated focal epileptiform discharges. Statistically significant differences were found between the control and study groups in regard to the following variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 22 publications
3
39
1
Order By: Relevance
“…Thus, 24% of these patients had complex partial seizures, 18% had hemiclonic and 10% adversive seizures with or without secondary generalization. This proportion is similar to those found by Gabor and Ajmone-Marsan (1969), who noted 14% with complex partial seizures and 25% with simple partial seizures with sensorimotor symptoms; and by Niedermeyer (1972), who found 23% with psychomotor seizures and 23% with focal motor, hemiconvulsive, or adversive seizures.…”
Section: Etiology Of Symptomatic Partial Epilepsies With Sbssupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, 24% of these patients had complex partial seizures, 18% had hemiclonic and 10% adversive seizures with or without secondary generalization. This proportion is similar to those found by Gabor and Ajmone-Marsan (1969), who noted 14% with complex partial seizures and 25% with simple partial seizures with sensorimotor symptoms; and by Niedermeyer (1972), who found 23% with psychomotor seizures and 23% with focal motor, hemiconvulsive, or adversive seizures.…”
Section: Etiology Of Symptomatic Partial Epilepsies With Sbssupporting
confidence: 86%
“…Mental retardation was found in 36%. Gabor and Ajmone-Marsan (1969) and Niedermeyer (1972) found 20% and 12% respectively with hemiplegia, and 17% and 12% respectively with mental retardation.…”
Section: Etiology Of Symptomatic Partial Epilepsies With Sbsmentioning
confidence: 94%
See 1 more Smart Citation
“…As has long been known [24], interictal focal abnormalities were frequent in our series (22% in CAE and 33% in JAE). Recently several studies have pointed out that focal and/or asymmetric abnormalities can be noted in patients with JME, another form of 1GE.…”
Section: Prognosis Of Absence Epilepsiessupporting
confidence: 52%
“…In contrast to the current study, Williamson et al (41) found contralateral seizure onsets in 13% of nonlesional, postoperatively SF temporal lobe patients. The appearance of multiple interictal spike foci or generalized spike-waves augur an unfavorable surgical outcome likely by representing multifocal epileptogenesis (55)(56)(57)(58).…”
Section: Scalp Eegmentioning
confidence: 99%